A red-shifted photochromic sulfonylurea for the remote control of pancreatic beta cell function. Issue 27 (11th March 2015) - Broichhagen, J.; Frank, J. A.; Johnston, N. R.; Mitchell, R. K.; Šmid, K.; Marchetti, P.; Bugliani, M.; Rutter, G. A.; Trauner, D.; Hodson, D. J.
Abstract : Heterocyclic azobenzene photoresponsive elements can be installed on sulfonylureas, yielding optical control over insulin release with yellow light. Abstract : Azobenzene photoresponsive elements can be installed on sulfonylureas, yielding optical control over pancreatic beta cell function and insulin release. An obstacle to such photopharmacological approaches remains the use of ultraviolet-blue illumination. Herein, we synthesize and test a novel yellow light-activated sulfonylurea based on a heterocyclic azobenzene bearing a push–pull system.